Eco-Friendly Practices in Certifed Green Hotels in Phuket A Case Study of Russian Tourists - Elizaveta Nosovkina (Prince of Songkla University, 2023)
Thesis (M.B.A., Hospitality and Tourism Management)--Prince of Songkla University, 2020